COMPREHENSIVE NURSING ASSESSMENT INSTRUMENT FOR THE MANAGEMENT OF DIABETES MELLITUS IN THE ELDERLY - Vitaliati, Trisna (Indonesian Journal of Community Health Nursing, 2026)
Introduction: The ability of the self and the implementation of family functions of the elderly with diabetes in the management of diabetes mellitus is essential to know because it can influence the elderly to take appropriate actions to get effective interventions and prevent complications from the disease. This study aims to determine the validity and reliability of a comprehensive nursing assessment instrument for the management of diabetes mellitus in the elderly.   Method: This study's design is descriptive, with a crossectional approach conducted on 30 elderly respondents with diabetes mellitus who meet the inclusion criteria. This research instrument was developed based on the theory of family-centered nursing and the functional consequences model, which was then carried out with construct validity and reliability tests.   Result: The results of the validity test of the comprehensive nursing assessment instrument in the management of diabetes mellitus in the elderly living with family for all statement items based on family-centered nursing and functional consequences. The results were valid, all statement items had an r value calculated > the r table, which was all more than 0.361. Meanwhile, the reliability test of the instrument found that all instruments were declared reliable, namely the Cronbach alpha value of the entire instrument was less than 0.7.   Conclusion: The comprehensive nursing assessment instrument developed can be used to see how efforts to handle diabetes mellitus in the order of education, research, and health services at the Health Center.   Keywords: Diabetes mellitus; disease management; elderly; family; self-ability.